Nonlinguistic Cognitive Impairment in Poststroke Aphasia: A Prospective Study. (March 2014) - El Hachioui, Hanane; Visch-Brink, Evy G.; Lingsma, Hester F.; van de Sandt-Koenderman, Mieke W. M. E.; Dippel, Diederik W. J.; Koudstaal, Peter J.; Middelkoop, Huub A. M.
Background and objectives . Information on cognitive impairment in aphasic patients is limited. Our aim was to investigate the prevalence and course of nonlinguistic cognitive impairments in the first year after stroke and their association with aphasia and functional outcome. Methods . We included 147 patients with acute aphasia. At 3 months and 1 year, we assessed cognition with a nonlinguistic cognitive examination including abstract reasoning, visual memory, visual perception and construction, and executive functioning. We assessed language with a verbal communication rating (Aphasia Severity Rating Scale), the ScreeLing (a linguistic-level screening test), and the Token Test. We evaluated functional outcome with the modified Rankin scale and registered the use of antidepressants. Results . In total, 107 (88%) patients had impairments in at least one nonlinguistic cognitive domain at 3 months and 91 (80%) at 1 year. The most frequently observed impairment concerned visual memory (83% at 3 months; 78% at 1 year) and the least frequent visual perception and construction (19% at 3 months; 14% at 1 year). There was improvement on all cognitive domains including language, except for abstract reasoning. Patients with persisting aphasia had lower cognitive domain scores, worse functional outcome, and were more often depressed than patients who had recovered from aphasia. Conclusions . Standard nonlinguistic cognitive examination is recommended in aphasic stroke patients. Nonlinguistic cognitive impairments are common and associated with poor functional outcome and depression, especially in patients with persisting aphasia.